Stepwise strategy for generating osteoblasts from human pluripotent stem cells under fully defined xeno-free conditions with small-molecule inducers - Zujur, Denise (Regen Ther, 2020)
Clinically relevant human induced pluripotent stem cell (hiPSC) derivatives require efficient protocols to differentiate hiPSCs into specific lineages. Here we developed a fully defined xeno-free strategy to direct hiPSCs toward osteoblasts within 21 days. The strategy successfully achieved the osteogenic induction of four independently derived hiPSC lines by a sequential use of combinations of small-molecule inducers. The induction first generated mesodermal cells, which subsequently recapitulated the developmental expression pattern of major osteoblast genes and proteins. Importantly, Col2.3-Cherry hiPSCs subjected to this strategy strongly expressed the cherry fluorescence that has been observed in bone-forming osteoblasts in vivo. Moreover, the protocol combined with a three-dimensional (3D) scaffold was suitable for the generation of a xeno-free 3D osteogenic system. Thus, our strategy offers a platform with significant advantages for bone biology studies and it will also contribute to clinical applications of hiPSCs to skeletal regenerative medicine.